Wyścigi motocyklowe Moto-Cross. (Malbrok : [s.n.], 1959)
Afisz inf. o wyścigach 12.04.1959 r. w Sopot Kamienny Potok.
Keywords: Wyścigi motocyklowe -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne